Ciało i sport w twórczości Jana Szymczyka w kontekście klasycznych i współczesnych koncepcji socjologii ciała - Adamczyk, Monika Dorota (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The aim of this article is to present Jan Szymczyk’s reflections on human corporeality and the relationship of somatization with sport and tourism. In some of his writings, Szymczyk systematically reflects on the status of the body in postmodernity and presents links between corporeality, sport and tourism. Like other theoreticians, Szymczyk noticed strong correlations of human corporeality with forms of physical activity such as sport and tourism. The article attempts to present the author’s achievements in this field, with particular emphasis on the multifaceted relations between tourism and sport, especially in the case of qualified tourism. The article discusses the development of the sub-discipline of sociology of the body, the objects of the sub-discipline, and finally Jan Szymczyk’s own efforts to prove the connection between sport, tourism and the mentioned sub-discipline of the sociology of the body.